The effects of energy price changes: heterogeneous welfare impacts and energy poverty in Indonesia - Renner, Sebastian; Lay, Jann; Schleicher, Michael (Environment and development economics, 2019)
We study the welfare and energy poverty implications of energy price change scenarios in Indonesia. Our analysis extends previous analyses of energy price impacts at the household level in three ways. First, by employing a household energy demand system (QUAIDS), we are able to distinguish between first- and second-order welfare effects over the income distribution. Second, our results point to the ownership of energy-processing durables as another source of impact heterogeneity. Third, we extend the welfare analysis beyond the money-metric utility effects and look at energy poverty, which is understood as the absence of or imperfect access to reliable and clean modern energy services. The analysis indicates that energy prices may serve as an effective instrument to reduce energy use but also have important adverse welfare effects. The latter can, however, be mitigated by appropriate compensation policies.